St Augustine's Doctrine of Eternal Punishment : His Biblical and Theological Argument. - Cho, Dongsun (Lewiston : Edwin Mellen Press, 2010)
The thesis of this work is that Augustine?s doctrine of eternal punishment is not the result of his employment of the Platonic concept of the immortal and divine soul but the product of his theological conviction, based on sound exegetical conclusions, that the Bible clearly teaches the eternity of hell.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- Saint; Hell -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Future punishment -- Christianity -- History of doctrines -- Early church, ca. 30-600.; RELIGION -- Christian Theology -- Eschatology; Electronic books